The Influence Of Business Strategy And Good Corporate Governance On Corporate Sustainability Performance: Coal Mining Listed On The Indonesia Stock Exchange - Muzakkir Muzakkir; Yanto Naim; Yusri Yusri; Ahmad Ahmad (Green Publisher Indonesia, 2024)
The coal mining industry plays an important role in the Indonesian economy, but also faces major challenges related to environmental and social sustainability. Thus, with increasing awareness of environmental and social issues, mining companies are expected to implement sustainable business strategies and good corporate governance (GCG) practices. The purpose of this study is to analyze the influence of business strategy and good corporate governance on the sustainability performance of coal mining companies. This type of research is descriptive research with a quantitative approach. Data collection techniques in this study are questionnaires and annual reports. The collected data were then analyzed using regression analysis. The results of the study indicate that business strategy and good corporate governance have an effect on the corporate sustainability of coal mining companies listed on the Indonesia Stock Exchange (IDX).